2020
DOI: 10.3390/su12176807
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ Involvement in E-Government in the European Union: The Rising Importance of the Digital Skills

Abstract: This paper studies what factors influence European citizens in their e-government adoption and use, and whether there are differences within the European Union. A binary logistic regression model has been used to determine the profile of e-government users. The article highlights especially the influence of digital skills, as an increasingly influential factor, and opens up new areas of research such as the uses of e-government depending on the population density or sociodemographic factors. Given a certain la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 80 publications
0
13
1
Order By: Relevance
“…The European Commission, the European Parliament and EU leaders agreed on a recovery plan that will lead the way out of the crisis and lay the foundations for a digital, greener and more sustainable Europe [29]. This is also a time during which citizens want to bridge digital divides and accelerate digital transformation, and three out of four Europeans think that there are 3 priority areas that need to be addressed-digital public services, digital skills and broadband internet access [30]. All of these factors lead us to believe that this is the right time to act even more decisively and bring best practices to the attention of the international community for widespread dissemination and to encourage the successful implementation of an integrated STEM program [31].…”
Section: Discussionmentioning
confidence: 99%
“…The European Commission, the European Parliament and EU leaders agreed on a recovery plan that will lead the way out of the crisis and lay the foundations for a digital, greener and more sustainable Europe [29]. This is also a time during which citizens want to bridge digital divides and accelerate digital transformation, and three out of four Europeans think that there are 3 priority areas that need to be addressed-digital public services, digital skills and broadband internet access [30]. All of these factors lead us to believe that this is the right time to act even more decisively and bring best practices to the attention of the international community for widespread dissemination and to encourage the successful implementation of an integrated STEM program [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this process of shaping Society 5.0 as a digital society, digital literacy is vital to foster involvement and stimulate social equity Rodriguez-Hevía, Navío-Marco, & Ruiz-Gómez, 2020;Tran et al, 2020;Gustiana, Wahyuni, & Hasti, 2019) (Figure 1). Yashalovaa, Shreidera, and Yakovlevab (2019) offer a systematic overview of the components of digital literacy regarding (i) digital consumption; (ii) digital competencies; and (iii) digital security.…”
Section: Nonhuman Beingsmentioning
confidence: 99%
“…In fact, various studies have found that a parent's education plays a significant role in their children's achievements. [28] Parents of higher educational levels always have greater success in providing their children with the necessary skills they need such that they can become successful easily when attain an academic setting. [29] As Acharya and Joshi [28] point out, educated parents like to transfer the value of education to their children that will strongly affect the aspiration level and achievement of their children.…”
Section: Computers and Digital Devicesmentioning
confidence: 99%